A Quantitative Approach to the Illustration of the Percentage-of-Completion Method. - Hawthorne, William H.; Herring III, Hartwell C.; De Coster, Don T. (The Accounting Review, 1975)
This article describes a generalized quantitative approach to the presentation of percentage-of-completion method for recognizing profit on long-term construction contracts. This method has two distinct advantages over the non-quantitative approach. First, the use of a programmable symbolic language permits the student to be appraised of the potential for determining profit on many contracts virtually instantaneously. Such an environment is realistic to many actual business situations. Second, this method permits attention to be focused on the conceptual aspects of the percentage-of-completion method and avoids the danger of centering attention on the arithmetic busy-work which is inherent in the non-quantitative approach. Essentially, the percentage-of-completion method is an attempt to recognize income in proportion to progress on a project for each year in which construction occurs. Relevant data for this calculation include estimated project life in years, contract price, expenditures in year i, and the estimated cost to complete the contract made in year i.